Treatment of the acute sickle cell vaso‐occlusive crisis in the Emergency Department: a Brazilian method of switching from intravenous to oral morphine. (19th March 2014) - Campos, Jessica; Lobo, Clarisse; Queiroz, Ana Maria Mach; do Nascimento, Emilia Matos; Lima, Carlos Bernardo; Cardoso, Gilberto; Ballas, Samir K.
Abstract Objectives Describe the treatment of patients with vaso‐occlusive crises (VOC) in a Brazilian emergency department (ED) and the successful switch from intravenous to oral morphine. Patients and methods We analyzed records of 315 patients with sickle cell disease using two different protocols for pain: one in March 2010 prescribing intravenous morphine every 4 h throughout their stay, and another in March 2011 and 2012 prescribing one initial dose of intravenous morphine followed by equianalgesic doses of oral morphine every 4 h. Patients were triaged into three groups: mild, moderate, and severe VOC. The mild group was treated within 1 h after triage, the moderate within 30 min and the severe was treated immediately. Patients whose pain was not relieved within 6 h after the first dose of morphine were transferred into a different holding area of the ED where they continued to receive the same treatment for 48 h after which they were hospitalized if still in pain. Results The number of patients who stayed <24 h in the ED increased significantly from 63 in 2010 to 87 in 2012, and the number of admissions decreased from 26 in 2010 to 10 in 2012. The incidence of acute chest syndrome decreased from 8.5% in 2010 to 1.9% in 2012. Conclusion Patients treated with oral morphine stayed a shorter time in the ED, had more pain relief, were admitted less frequently, and had less acute chest syndrome. These differences may be due to environmental, cultural, psychological, and pharmacogenetic factors.